2016
DOI: 10.1177/0956462416646492
|View full text |Cite
|
Sign up to set email alerts
|

HIV-related mortality at a district hospital in Botswana

Abstract: We reviewed mortality data among medical inpatients at a tertiary hospital in Botswana to identify risk factors for adverse inpatient outcomes. This review was a prospective analysis of inpatient admissions. All medical admissions to male and female medical wards were recorded over a six-month period between 1 November 2011 and 30 April 2012. Data collected included patient demographics, HIV status (positive, negative, unknown), HIV testing history, HIV related treatment and serological history, admission and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The overall mortality rate was somewhat higher (19.4% versus 14.6%), but mortality among HIV-infected patients was similar (23.7% versus 24.2%) compared to prior to PITC [ 3 ]. Compared to studies within the country and region, our medical ward mortality rate was similar to that reported in South Africa (17%) [ 17 ], Botswana (23%) [ 18 ] and Blantyre, Malawi (22.7%) [ 15 ] within a period of PITC and early ART scale-up. The mortality rate among HIV positive patients in our study was lower than that found in a recent systematic review and meta-analysis of 31% within Africa [ 20 ] but was somewhat consistent with a mortality rate range of 24.2% to 44% within SSA reported in another study [ 16 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The overall mortality rate was somewhat higher (19.4% versus 14.6%), but mortality among HIV-infected patients was similar (23.7% versus 24.2%) compared to prior to PITC [ 3 ]. Compared to studies within the country and region, our medical ward mortality rate was similar to that reported in South Africa (17%) [ 17 ], Botswana (23%) [ 18 ] and Blantyre, Malawi (22.7%) [ 15 ] within a period of PITC and early ART scale-up. The mortality rate among HIV positive patients in our study was lower than that found in a recent systematic review and meta-analysis of 31% within Africa [ 20 ] but was somewhat consistent with a mortality rate range of 24.2% to 44% within SSA reported in another study [ 16 ].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, the HIV prevalence rate was also comparable to a study done in Blantyre, Malawi within an era of PITC and ART scale-up where they found 4551/10191 (44.7%) positive patients [ 15 ]. However, the prevalence rate was lower compared to some countries within the region; South Africa (60.1%) [ 17 ] and Botswana (47.5%) [ 18 ]. The HIV prevalence rates among inpatients in Malawi has improved compared to the pre-ART era (70%) [ 19 ] highlighting the progress in the country’s ART program.…”
Section: Discussionmentioning
confidence: 99%
“…We compared our results with those of similar surveillance conducted at SLH over a 6‐month period between November 2011 and April 2012 .During the current surveillance period, overall final HIV prevalence was lower (42.4% vs. 47.6% of admissions, p < 0.01) and the proportion of patients with unknown HIV status on admission declined (36.1 vs. 41.2% p < 0.01) as did the proportion of patients whose HIV status was unknown at discharge or death (10.7% vs. 27.7% p < 0.0001). Among HIV‐positive admissions in the current surveillance period, ART‐coverage was higher (72.2% vs. 56.2%, p < 0.0001), mortality was similar (22.2% vs. 22.7%, p = 0.93), tuberculosis diagnoses increased (27.5% vs. 20.1%, p < 0.01) and tuberculosis associated mortality was higher (35.9% vs. 24.7%, p = 0.05).…”
Section: Resultsmentioning
confidence: 95%
“…Perry& al. reported a low CD4 cell count (<200 cells/mm 3 ) as a higher risk of death [25]. Such dissimilarities could be explained in our series by the low rate of achievement of CD4 count and the homogeneity of the targeted population who was mostly at an advanced WHO stage.…”
Section: Discussionmentioning
confidence: 48%